Relationship between exercise habits and social isolation in older patients with predialysis CKD: a cross-sectional study - Aki Tabata; Hiroki Yabe; Takehide Katogi; Yuya Mitake; Shunta Oono; Tomoya Yamaguchi; Takayuki Fujii (Renal Replacement Therapy)
Abstract Background Maintaining exercise habits in older patients with predialysis chronic kidney disease (CKD) is important to prevent conversion to renal replacement therapy and improve prognosis. This study identified factors influencing exercise habits in older patients with predialysis CKD. Methods This cross-sectional study included 113 patients aged ≥ 65 years with stages 3–5 predialysis CKD who were admitted for CKD education purposes. Exercise habits were assessed using the transtheoretical model. Social isolation was assessed using the Lubben Social Network Scale (LSNS-6). Furthermore, the short physical performance battery (SPPB) and grip strength, exercise self-efficacy (SE), hemoglobin, and estimated glomerular filtration rate of the participants were assessed. Results Among the 55 patients who maintained exercise habits, 20 (57.1%) were at CKD stage 3, 19 (43.2%) were at CKD stage 4, and 16 (47.1%) were at CKD stage 5. The LSNS-6, SPPB, grip strength, and exercise SE scores significantly differed between the with exercise habits group and without exercise habits group (p < 0.05). The multivariate logistic regression analysis results indicated that the LSNS-6 (OR:1.10; 95%CI:1.022–1.210) and exercise SE (OR:1.10; 95%CI:1.009–1.199) were significantly associated with exercise habits (p < 0.05). Conversely, no significant associations were found between exercise habits and SPPB, grip strength, renal function, or anemia. Conclusions Social isolation and SE may be an important factor influencing exercise habits in older patients with predialysis CKD.